2006
DOI: 10.1103/physrevb.74.214113
|View full text |Cite
|
Sign up to set email alerts
|

Size and doping effects on the coercive field of ferroelectric nanoparticles: A microscopic model

Abstract: A microscopic model for describing ferroelectric nanoparticles is proposed which allows us to calculate the polarization as a function of an external electric field, the temperature, the defect concentration and the particle size. The interaction of the constituents of the material, arranged in layers, depends on both the coupling strength at the surface and that of defect shells in addition to the bulk values. The analysis is based on an Ising model in a transverse field, modified in such a manner to study th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Figure 4c shows the calculated lattice parameters and tetragonality (c/a) of PST films, which is consistent with the report by Chu et al [18] for pure PbTiO 3 . The significant reduction in the value of c/a with Sr concentration is due to the closely matched ionic radii of both Pb (1.33 Å ) and Sr (1.32 Å ), which can slow down the diffusion rate of Sr 2 þ and Pb 2 þ ions, resulting in small grains and consequent low growth along the c-axis [22]. The average grain size was obtained from the Scherer relation and their mean values are given in Table 1.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 4c shows the calculated lattice parameters and tetragonality (c/a) of PST films, which is consistent with the report by Chu et al [18] for pure PbTiO 3 . The significant reduction in the value of c/a with Sr concentration is due to the closely matched ionic radii of both Pb (1.33 Å ) and Sr (1.32 Å ), which can slow down the diffusion rate of Sr 2 þ and Pb 2 þ ions, resulting in small grains and consequent low growth along the c-axis [22]. The average grain size was obtained from the Scherer relation and their mean values are given in Table 1.…”
Section: Resultsmentioning
confidence: 97%
“…16,17 For subwavelength apertures, the basic twodimensional ͑2D͒ TE 1,0 mode plays an important role in the process of extraordinary transmission. 18 For coaxial apertures, many theoretical [19][20][21][22] and experimental [23][24][25] studies of their transmission properties have been reported. It has been found that some transmission peaks in annular circular apertures are attributed to the resonances of TE m,1 guide modes.…”
Section: Light Transmission Through Metallic Two-dimensional Arrays Omentioning
confidence: 99%
“…1 In view of the sustained trend toward further miniaturization of electronic devices, the investigation of surface and size effects in ferroelectric thin films is practically important. There have been a lot of experimental [2][3][4][5][6][7][8][9][10] and theoretical [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] efforts devoted to study these important effects.…”
Section: Introductionmentioning
confidence: 99%